2024
DOI: 10.3389/fncel.2024.1358450
|View full text |Cite
|
Sign up to set email alerts
|

The role of glial cells in mental illness: a systematic review on astroglia and microglia as potential players in schizophrenia and its cognitive and emotional aspects

Daniela Laricchiuta,
Martina Papi,
Davide Decandia
et al.

Abstract: Schizophrenia is a complex and severe mental disorder that affects approximately 1% of the global population. It is characterized by a wide range of symptoms, including delusions, hallucinations, disorganized speech and behavior, and cognitive impairment. Recent research has suggested that the immune system dysregulation may play a significant role in the pathogenesis of schizophrenia, and glial cells, such as astroglia and microglia known to be involved in neuroinflammation and immune regulation, have emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
0
0
Order By: Relevance
“…Although there is considerable disagreement in the literature, several postmortem studies on schizophrenia have reported changes in astrocytic density and/or astrocytic markers in schizophrenia [ 61 ]. Laricchiuta et al [ 72 ] discuss the confounding factors that make clinical studies on astrocytic and microglial markers in schizophrenia difficult.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Although there is considerable disagreement in the literature, several postmortem studies on schizophrenia have reported changes in astrocytic density and/or astrocytic markers in schizophrenia [ 61 ]. Laricchiuta et al [ 72 ] discuss the confounding factors that make clinical studies on astrocytic and microglial markers in schizophrenia difficult.…”
Section: Neuroinflammationmentioning
confidence: 99%